A study on Talent Management Analysis in D2D business school - Naik, Dr. Shruti D (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study is to outline the findings based on the case study and suggest needed HR improvements and initiatives to be carried out by D2D business school in order to achieve its goals. A famous business school from Hyderabad was used for the study. The business school intends to expand its focus to international students and thereby increase the student strength to around 600.In order to support the additional students, there is a plan to increase the number of Management Faculty from 19 to 25, hence the requirement for the study. The paper focuses on study of itsTalent Management Analysis and thereby providing important and relevant findings and further providing suggestions for further HR improvements and finally a few relevant and innovative proposed initiatives to be carried out by the business school.